Effects of detraining on neuromuscular performance in a selected group of elite women pole-vaulters: a case study - Loturco, I.; Pereira, L. A.; Kobal, R.; Martins, H.; Kitamura, K.; Cal Abad, C. C.; Nakamura, F. Y. (The Journal of Sports Medicine and Physical Fitness, 2017)
AIM: to determine the effects of 28 days of inactivity on neuromuscular performance of elite women pole-vaulters.